Genome- wide characterization of Nuclear Factor Y (NF-Y) gene family of sorghum [Sorghum bicolor (L.) Moench]: a bioinformatics approach - Malviya, Neha (Physiol Mol Biol Plants, 2016)
Nuclear factor Y (NF-Y) is a heterotrimeric transcription factor (TF) complex with preferential binding to CCAAT elements of promoters, regulating gene expression in most of the higher eukaryotes. The availability of plant genome sequences have revealed multiple number of genes coding for the three subunits, namely NF-YA, NF-YB and NF-YC in contrast to single NF-Y gene for each subunit reported in yeast and animals. A total of 33 NF-YTF comprising of 8 NF-YA, 11 NF-YB and 14 NF-YC subunits were accessed from the sorghum genome. The bioinformatic characterization of NF-Y gene family of sorghum for gene structure, chromosome location, protein motif, phylogeny, gene duplication and in-silico expression under abiotic stresses have been attempted in the present study. The identified SbNF-Y genes are distributed on all the 10 chromosomes of sorghum with variability in the frequency and 18 out of 33 SbNF-Ys were found to be intronless. Segmental duplication event was found to be predominant feature based on gene duplication pattern study. Several orthologs and paralogs groups were disclosed through the comprehensive phylogenetic analysis of SbNF-Y proteins along with 36 Arabidopsis and 28 rice NF-Y proteins. In-silico expression analysis under abiotic stresses using rice transcriptome data revealed several of the sorghum NF-Y genes to be associated with salt, drought, cold and heat stresses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12298-016-0349-z) contains supplementary material, which is available to authorized users.